Storytelling-Based Learning Videos to Improve Student Learning Outcomes in Elementary Schools - Wirayanti Nona Alor Usman; I Nyoman Jampel; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2025)
This study was motivated by the relatively low learning outcomes of elementary school students, which are influenced by less engaging instructional processes and the limited use of interactive learning media. Therefore, innovative learning media such as storytelling-based instructional videos are needed to enhance students’ understanding and learning outcomes. This study aims to analyze the feasibility, practicality, and effectiveness of storytelling-based instructional videos in improving the English learning outcomes of third-grade students. The development model employed in this study was ADDIE. The research subjects consisted of 37 third-grade students who participated in both small-scale and large-scale trials. Data were collected through validation questionnaires completed by material experts, media experts, and instructional design experts, as well as response questionnaires from students and teachers. In addition, learning outcome data were obtained through pre-test and post-test assessments. Data analysis was conducted using qualitative descriptive analysis, quantitative descriptive analysis, the Wilcoxon Signed-Rank Test, and N-gain calculations. The results indicate that the developed instructional video received a “very good” rating from experts, while student and teacher responses were categorized as very positive. Furthermore, the effectiveness test showed a high category improvement in students’ learning outcomes. These findings demonstrate that storytelling-based instructional videos are valid, practical, and effective in improving elementary school students’ English learning outcomes. The study also implies that integrating storytelling into audiovisual media can create more interactive, enjoyable, and meaningful learning experiences for elementary school students in the digital era.